Loss of FoxOs in muscle reveals sex-based differences in insulin sensitivity but mitigates diet-induced obesity - Christie M. Penniman; Pablo A. Suarez Beltran; Gourav Bhardwaj; Taylor L. Junck; Jayashree Jena; Kennedy Poro; Michael F. Hirshman; Laurie J. Goodyear; Brian T. O'Neill (Elsevier, 2019)
Objective: Gender influences obesity-related complications, including diabetes. Females are more protected from insulin resistance after diet-induced obesity, which may be related to fat accumulation and muscle insulin sensitivity. FoxOs regulate muscle atrophy and are targets of insulin action, but their role in muscle insulin sensitivity and mitochondrial metabolism is unknown. Methods: We measured muscle insulin signaling, mitochondrial energetics, and metabolic responses to a high-fat diet (HFD) in male and female muscle-specific FoxO1/3/4 triple knock-out (TKO) mice. Results: In male TKO muscle, insulin-stimulated AKT activation was decreased. AKT2 protein and mRNA levels were reduced and insulin receptor protein and IRS-2 mRNA decreased. These changes contributed to decreased insulin-stimulated glucose uptake in glycolytic muscle in males. In contrast, female TKOs maintain normal insulin-mediated AKT phosphorylation, normal AKT2 levels, and normal glucose uptake in glycolytic muscle. When challenged with a HFD, fat gain was attenuated in both male and female TKO mice, and associated with decreased glucose levels, improved glucose homeostasis, and reduced muscle triglyceride accumulation. Furthermore, female TKO mice showed increased energy expenditure, relative to controls, due to increased lean mass and maintenance of mitochondrial function in muscle. Conclusions: FoxO deletion in muscle uncovers sexually dimorphic regulation of AKT2, which impairs insulin signaling in male mice, but not females. However, loss of FoxOs in muscle from both males and females also leads to muscle hypertrophy and increases in metabolic rate. These factors mitigate fat gain and attenuate metabolic abnormalities in response to a HFD. Keywords: FoxO, Gender differences, Sexual dimorphism, Insulin resistance, Muscle hypertrophy, High-fat diet, Glucose uptake, Diet-induced obesity